Enhancing Senior High School Students' Mathematical Communication Skills in Problem Solving Through Scaffolding - Hadi Hadi; Elly Susanti Susanti; Sri Harini Harini (IAIN Manado, 2025)
This study aims to describe the transformation of mathematical communication skills in high school students through the use of problem-solving scaffolding. Transformation is interpreted as a change in the way students convey mathematical ideas and solutions through writing, visuals, and symbols. The study employed a descriptive qualitative approach, utilizing data from TPMKM, think-aloud sessions, and semi-structured interviews. The analysis was carried out based on the Polya stages and source triangulation. The results showed that students in the low category before scaffolding only met the written text (Wr1) and partial mathematical expression (Me) indicators. After scaffolding, they meet Wr1, Wr2, Wr3, Dr, and Me more completely. Meanwhile, students in the medium category initially met Wr1, part of Wr2, and part of Me. After scaffolding, they showed significant changes: they were able to meet Wr1, Wr2, Wr3, Dr, and Me in their entirety. This transformation reflects a process of assimilation, accommodation, and equilibrium, which changes the student's categories from low to medium and from medium to high.